The Effect of Forecrop and Plant Protection on the Pathology Parameters and Yields of Winter Wheat - Hornok, Mária; Pepó, Péter (Acta Agraria Debreceniensis, 2005)
We carried out our experiment in the cropyears of 2000/2001, 2001/2002 and 2002/2003, on calcareous chernozem soil, at the experimental site of the Debrecen University Farm and Regional Research Institute, at Látókép. We examined the disease resistance and the yield quantity of Mv Magvas variety by adopting different forecrops and plant protection technologies, at 30+30 N level and at normal cereal row spacing. We applied two forecrops (wheat and pea) and two plant protection technologies (extensive and intensive). We measured the rate of infection by population survey in the first ten days of June.In the course of our examinations, we found, that the rate of powdery mildew infection was higher in the thicker population sown after pea forecrop in all three years, as powdery mildew is not a typical cereal disease.The infection rate of leaf mildew and DTR (Dreschlera tritici-repentis) was higher after wheat forecrop in all examined years, because these are typical wheat diseases and infection centres in the soil promote the spreading of these diseases. However, it was possible to parry the adverse effect of forecrops by intensive plant protection.Due to the chernozem soil, wich has good water management features, and due to the good preparation of the seedbed, the effect of forecrops on yield quantity did not appear in the examined years. The quantity of the yield was only slightly larger after pea forecrop in the cropyears of 2000/2001 and 2002/2003 than after wheat. Nonetheless, the data of technical literatures state that the yield quantity can be larger, even by 15-20%, after pea forecrop.In the course of intensive plant protection technology, we applied systemic pesticides, while in the course of environmentally sound technology, we used contact pesticides of sulphur content. In those populations that were treated with environmentally sound plant protection technology, infection rate was higher in all three years.Yield quantities were somewhat lower in the course of applying extensive, environmentally sound technology, because diseases appeared in these populations to the higher degree. Powdery mildew does not, but leaf mildew and Dreschlera tritici-repentis have a significant yield decreasing effect. With appropriate, well-selected fungicides, we were able to keep every leaf diseases well in hand, and the rate of infection was almost independent of the influence of the breeding year.